EVE OUT OF AFRICA, ADAM OUT OF ASIA: The first human immigration to Southeast Asia and the transition to Homo sapiens sapiens in place - Müller-Beck, Hansjürgen (Hukay; Vol 3 No 1)
The first human immigration to Southeast Asia and the transition to Homo sapiens sapiens in place.